A Suitcase Surprise for Mommy - Cora, Cat; Allen, Joy (New York : Dial Books for Young Readers, 2011)
When Mommy has to travel for work, her son gives her a special picture to ease their temporary separation.
Keywords: Mother-son relationship -- Fiction; Separation anxiety in children -- Fiction